Effect of nutrition support team on 28-day mortality in Korean patients with acute respiratory failure - Inhan Lee; Junghyun Kim; Mihyun Ku; Yurim Choi; Sohyun Park; Jihyeon Bang; Joohae Kim (Acute and Critical Care)
Background Providing optimal nutrition to patients with acute respiratory failure is difficult because nutritional requirements vary according to disease severity and comorbidities. In 2021, the National Medical Center initiated a protocol for screening upon admission and regular monitoring by a multidisciplinary nutritional support team (NST), for all patients in the medical intensive care unit (ICU). This study aimed to evaluate the effects of routine NST monitoring and active intervention on the clinical outcomes of patients with acute respiratory failure. Methods Patients with acute respiratory failure requiring high-flow nasal cannula, non-invasive ventilation, or mechanical ventilation were included. The primary outcome was 28-day mortality after ICU admission. Secondary outcomes included the supplied/target calorie ratio, supplied/target protein ratio on day 7, and complications. Results In total, 152 patients were included in the analysis. The patients were divided into a pre-monitoring (n=96) and post-monitoring groups (n=56). More patients in the post-monitoring group received NST intervention and had earlier initiation of enteral feeding. In survival analysis, 28-day mortality was significantly lower in post-monitoring group (adjusted hazard ratio, 0.42; 95% CI, 0.24–0.74). The ratio of achievement for required calories and protein on day 7 was higher, but not significantly, in the post-monitoring group. No significant differences were observed in the incidence of complications. Conclusions Regular NST monitoring in the ICU could have contributed to a reduced risk of 28-day mortality in critically ill patients with acute respiratory failure.